Analisis Kinerja Halte Trans Metro Dewata - Moi, Fransiska; Hermawati, Putu; Aryawan, I Gede Made Oka (Jurnal Talenta Sipil, 2024)
Trans Metro Dewata is an Integrated Highway Bus transportation system operating since September 2020 in Bali, which is a program of the Indonesian Ministry of Transportation through the Directorate General of Land Transportation. Until now it has not been much in demand by the people in Bali, one of the causes is inadequate bus stop facilities. The condition and performance of the trans metro dewata bus stop that is used as the object of research are not all in accordance with the Minimum Service Standards (SPM). The level of public satisfaction as users of the Trans Metro Dewata bus stop can be concluded that as many as 59% are dissatisfied with the availability of security officers and security disturbance information, 59% are dissatisfied with the availability of cleaning facilities when using the bus stop, 57% are dissatisfied with the availability of lighting at the bus stop, 45% are quite satisfied with the facilities for going up and down stairs, 57% are not satisfied with the availability of service information and 39% are quite satisfied with the adequacy of time bus stop.